Break Even Point Analysis of Flower Bucket Business Hellokadoku Payabakung Village, Deli Serdang Regency - Della Chastika; Rara Ivanka; Hasbiyana Haudi Nasution; Dwi Saraswati (International Journal of Economics, Management and Accounting, 2025)
The purpose of establishing a business is to gain profit or profit that can be used for survival. Likewise with the Flower Bucket Business "Hellokadoku" Payabakung Village, Deli Serdang Regency . This study aims to determine the value or point of Break Even Point in this business. This analysis is one of the tools used by the company's management to be able to do this to help in knowing how much a certain level of sales is, so that the company does not make a profit and also does not experience a loss (break even). The type of research used in this study is descriptive research with quantitative. With this approach, the data source used is secondary data. Based on the results of the analysis, it can be seen that the BEP value of the Flower Bucket Business "Hellokadoku" in units of 24 pcs and if expressed in rupiah is Rp. 3,529,411.